TUBERCULOSIS IN LIVER TRANSPLANT RECIPIENT : A SYSTEMATIC REVIEW - Nur Amelia, Devita (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Background: Despite claims, transplant recipients' TB rates are random. The rate of posttransplant tuberculosis depends on the organ transplanted, pre-transplant latent tuberculosis screening, and previous antituberculosis medication. This rate may also depend on recipient and donor tuberculosis rates. Active tuberculosis after solid organ transplantation increases the risk of graft loss and death four-fold compared to the general population.Aim: This article examines the link between tubercolis and liver transplant recipient. Methods: This study showed that it met all of the requirements by looking at the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. So, the experts could make sure that the study was as current as possible. The search method used a number of electronic reference databases, such as Pubmed and SagePub, to look for papers that were published between 2000 and 2023. We didn't look at review papers, articles that had already been published, or articles that were only half done. Result: In the PubMed database, the results of our search brought up 66 articles, whereas the results of our search on SagePub brought up 23 articles. The results of the search conducted for the last year of 2013 yielded a total of 23 articles for PubMed and 18 articles for SagePub. In the end, we compiled a total of 20 papers, 16 of which came from PubMed and four of which came from SagePub. We included five research that met the criteria.Conclusion: Patients who have undergone organ transplantation are at high risk of developing latent TB. This shows the importance of administering prophylactic drugs such as isoniazid in post-liver transplant patients.